Art, politics and society in Julio Cortázar´s short-story «Instructions on how to kill ants in Rome» (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2024)
«Instructions on how to kill ants in Rome» by Julio Cortázar (Belgium, 1914 – France, 1984) serves as a study case that focuses on the literary and the social aspect of the short story. To begin with, contemporary symbolisms and reflections of his time are highlighted with the objective of highlighting them. By delving into the way, the story is in dialogue with its time, with the events of the past and those of the future, said reflections can be analyzed. Both the urban environment and the sociohistorical context are considered by way of examining closely the Cortazarian universe. The singularity of this short story, which belongs to the collection Cronopios and Famas (1962), leads to complex musings coming from the socio-political, philosophical and artistic space. As a result, the analysis is approached through a process that allows each person to draw their own conclusions through a subjective view based on an approach that builds new interpretations and interdisciplinary connections. In addition, the sociocultural origins and commitments of the writer, his outstanding career as a representative of his generation and the contemporary Latin American narrative are presented. To conclude, the imaginary space and the limits of reality are examined, while Rome becomes the starting point of an analysis that enables the emergence of new correlations that extend beyond geographical borders, combining the real with the fantastic, the artistic with the theoretical.